2017
DOI: 10.5858/arpa.2016-0057-ra
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Classification of Thymic Epithelial Tumors in the Era of Dr Thomas V. Colby

Abstract: Context.-Numerous histomorphologic and staging classifications of thymic epithelial tumors (TETs) have been proposed during the last century, suggesting that the classification of these tumors is challenging and controversial. Difficulties of classifying TETs include various combinations of epithelial cells and lymphocytes and the paucity of these tumors. The prognostic significance, specifically of the histomorphologic classifications, has been debated. Early classifications were also challenged by the uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…The absence of thymic carcinomas in our surgically resected cases may be because these cases present at an advanced stage of the disease when surgical resection may not be a treatment option. Global data have reported no sex predilection for TETs; however, the Indian studies had shown male predominance similar to the observation in the present series101415171823. Only two studies from India demonstrated a female-predominant population1316.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The absence of thymic carcinomas in our surgically resected cases may be because these cases present at an advanced stage of the disease when surgical resection may not be a treatment option. Global data have reported no sex predilection for TETs; however, the Indian studies had shown male predominance similar to the observation in the present series101415171823. Only two studies from India demonstrated a female-predominant population1316.…”
Section: Discussionsupporting
confidence: 82%
“…The morphological classification and staging of thymomas have been extensively debated upon since decades26, with at least 24 histomorphological classifications and 15 staging systems proposed till date10. In our study, the latest modifications of WHO 2015 classification of TETs was applied which also led to the reclassification of 24 cases2727.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, most studies demonstrate that MG prevalence on thymoma patients ranges from 30% to 50% [2]. Although there is still no consensus on an official staging classification system for thymic malignancies [3], the system originally developed by Masaoka et al [4] and subsequently modified by Koga et al [5] remains as the most widely accepted. This system (hereafter called Masaoka-Koga) establishes four stages based on the local extent of the disease [6].…”
Section: Introductionmentioning
confidence: 99%
“…On histology, the thymomas, in general, are seen to be composed of epithelial cells and lymphocytes in varying proportions. However, this seemingly innocuous admixture has led to several classification systems over decades5. The classification used currently and in this article by Guleria et al 2 is the WHO 20156, which identifies five subtypes (A, AB, B1, B2 and B3) depending on the morphology of the epithelial cells (spindloid cells, epithelioid cells or their combinations) and proportion of lymphocytes.…”
mentioning
confidence: 99%